Модернізація Конституції України: досвід, сучасність та перспективи - Крусян, Анжелика Романовна; Крусян, Анжеліка Романівна; Krusyan, Аnjelika R. (My University, 2012)
The article is devoted to the modernization of the Constitution in the process of constitutional reform and modernization (constitutional changes) in Ukraine. The article provides a theoretical and practical analysis of the constitutional draft work and the Law of Ukraine on introducing amendments to the Constitution of Ukraine at all stages of the Constitutional reforms in Ukraine. The article outlines the main trends in updating the Constitution and concludes on the need of the improvement of the Constitution in order to create Modern Ukrainian Constitutionalism, accounting for modern Constitutional legal realia.
Крусян А. Р. Модернізація Конституції України: досвід, сучасність та перспективи / А. Р. Крусян // Наукові праці Національного університету «Одеська юридична академія» : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю. П. Аленін [та ін.] ; відпов. за вип. В. М. Дрьомін ; МОНмолодьспорт України, НУ «ОЮА». – Одеса : Юрид. л-ра, 2012. – Т. 11. – С. 235-247.
Keywords: модернізація Конституції; Конституція України; конституційна реформа; конституційна модернізація; конституційні перетворення; сучасний український конституціоналізм; модернизация Конституции; Конституция Украины; конституционная реформа; конституционная модернизация; конституционные преобразования; современный украинский конституционализм; modernization of the Constitution; Constitution of Ukraine; Constitutional reform; Constitutional modernization; Constitutional changes; Modern Ukrainian Constitutionalism